Penerapan Standar Akuntansi Entitas Mikro, Kecil dan Menengah (SAK EMKM) dalam Meningkatkan Kualitas Laporan Keuangan: Studi Kasus Toko Podho Bungahe Tulungagung - Herawati, Hanan Maya; Priantilianingtiasari, Ruly (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The problem discussed in this study is the importance of recording financial reports in MSMEs according to applicable accounting standards, namely SAK EMKM, but in reality not all MSMEs are able to implement it. The purpose of this study was to determine the application of SAK EMKM in improving the quality of financial statements at Toko Podho Bughahe Tulungagung. The type of research used is field research with a descriptive qualitative approach. The data collection technique that the author uses is through interviews with the owner, treasurer and financial staff at Toko Podho Bughahe Tulungagung. The results showed that the application of financial statements that apply SAK EMKM has a better level of quality than ordinary financial statements. As applied by Toko Podho Bughahe Tulungagung, it has been able to implement quality financial reports through the existence of financial accounting standards, namely SAK EMKM. Keywords : Quality of financial statements, SAK EMKM.